2014
DOI: 10.1038/onc.2014.270
|View full text |Cite
|
Sign up to set email alerts
|

hTERT mediates norepinephrine-induced Slug expression and ovarian cancer aggressiveness

Abstract: Stress hormones have been implicated in both tumor initiation and progression. Human telomerase reverse transcriptase (hTERT) is overexpressed in cancer cells and associated with malignant tumor progression and poor outcome. We thus sought to determine whether the stress hormone norepinephrine (NE) could induce hTERT expression and subsequently ovarian cancer progression. Unexpectedly, NE induced hTERT transcript and protein expression, and subsequently ovarian cancer cell invasion. Pharmacologic inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 51 publications
1
80
0
Order By: Relevance
“…In addition, our previous study showed that NE induces ovarian cancer cell EMT through upregulating Slug expression (Choi et al 2015). We therefore determined whether REV inhibits NE-induced ovarian cancer cell EMT.…”
Section: Rev Inhibits Ne-induced Ovarian Cancer Cell Emtmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, our previous study showed that NE induces ovarian cancer cell EMT through upregulating Slug expression (Choi et al 2015). We therefore determined whether REV inhibits NE-induced ovarian cancer cell EMT.…”
Section: Rev Inhibits Ne-induced Ovarian Cancer Cell Emtmentioning
confidence: 99%
“…1a). Given that chronic stress hormone NE is associated with tumorigenecity and ovarian cancer progression (Nilsson et al 2007;Shahzad et al 2010;Armaiz-Pena et al 2013;Choi et al 2015), we next examined the effect of REV on NE-induced ovarian cancer cell invasion. Stimulation of the cells with NE strongly increased ovarian cancer cell invasiveness (Fig.…”
Section: Rev Inhibits Ne-induced Ovarian Cancer Cell Invasionmentioning
confidence: 99%
See 3 more Smart Citations